2001
DOI: 10.1046/j.1471-4159.2001.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of functional N‐methyl‐d‐aspartate receptors in neurons by RNase P‐mediated cleavage of the NR1 mRNA

Abstract: One approach to studying the functional role of individual NMDA receptor subunits involves the reduction in the abundance of the protein subunit in neurons. We have pursued a strategy to achieve this goal that involves the use of a small guide RNA which can lead to the destruction of the mRNA for a speci®c receptor subunit. We designed a small RNA molecule, termed`external guide sequence' (EGS), which binds to the NR1 mRNA and directs the endonuclease RNase P to cleave the target message. This EGS has exquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Kalb and his collaborators (66) have also shown that a recombinant HSV that contains an EGS directed to the mRNA of an N-methyl-D-aspartate receptor can infect primary cultures of neuronal cells and reverse some aspects of the cytotoxic effect of Nmethyl-D-aspartate receptor ligands.…”
Section: Minireview: Rnase P: Variations and Uses 6760mentioning
confidence: 99%
“…Kalb and his collaborators (66) have also shown that a recombinant HSV that contains an EGS directed to the mRNA of an N-methyl-D-aspartate receptor can infect primary cultures of neuronal cells and reverse some aspects of the cytotoxic effect of Nmethyl-D-aspartate receptor ligands.…”
Section: Minireview: Rnase P: Variations and Uses 6760mentioning
confidence: 99%
“…Indeed, our results confirm the utility of this promoter for the expression of the EGS genes in maize BMS cells. U3 snRNA is transcribed by pol III (RNA polymerase III) in plants, and its promoter was chosen for the expression of EGSs rather than a pol II promoter for several reasons [11][12][13][21][22][23]. First, the regulatory elements in this pol III promoter reside entirely upstream of the coding regions of the gene.…”
Section: Expression Of Egss In Vivomentioning
confidence: 99%
“…Although the EGS method might perform better in planta than one might anticipate from our transient assay results, it is important to appreciate that even a decrease of 70 % protein levels is adequate to begin establishing gene-function relationships or for use in metabolic engineering applications. One study that employed RNAi for disrupting expression of a transcription factor [29] and another that employed the EGS approach for downregulating the mRNA for a neuronal receptor [13] were both able to elicit the expected phenotypic alterations even when gene expression was reduced by only 50-60 %. Moreover, it has been documented that metabolic flux alterations can be accomplished even with an approx.…”
Section: Conclusion and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…This conserved mechanism can be directed against specific mRNA by providing a complementary external guide sequence (EGS), which binds to the target mRNA and directs RNase P cleavage (Li et al, 1992). When given the proper EGS, RNase P is able to catalytically break down bacterial, viral, and eukaryotic mRNAs (Guerrier-Takada et al, 1995; Guerrier-Takada et al, 1997; Jiang et al, 2012; Trang et al, 2001; Yen et al, 2001). Currently, EGSs can be created using phosphorodiamidate morpholino oligonucleotides (MOs), conjugated with a cell-penetrating peptide (CPP) to improve intracellular transport, and then used to alter and kill both Gram positive and negative bacteria (Shen et al, 2009; Wesolowski et al, 2011).…”
mentioning
confidence: 99%